'Digital tech' and the public sector: what new role after public funding?. Issue 5 (4th May 2017) - Cooke, Philip
ABSTRACT: Innovation scholars have long recognized entrepreneurship is 'imitative', whereas the commercialization of novelty is 'innovative'. Thus they are highly distinctive skill-sets. Entrepreneurship, first, involves optimizing market sentiment for pure profit sometimes to the point of catastrophe and even fraudulence in many markets. These include: payment protection insurance (PPI) to 'flash crashes', automotive emission 'defeat devices', corporate bribery settlements, social media 'hacking', 'fake news' and a litany of other infractions and catastrophes. Innovation, by contrast, is more explorative and team-reliant. Even if patenting betrays the hope for commercialization on markets, patented innovation frequently fails. Some academic innovators even profess a preference for prizes over profits. Second, this means that collective 'bonding' among entrepreneurs, in the form of claimed 'entrepreneurial ecosystems', is often based on a single customer platform or as a supplier of a highly specialist type of 'imitative' service from identikit pizza chains to 'me-too' smartphone apps. Through the latter, fused with artificial intelligence some interactive machine-learning services have long-existed as 'postsocial' algorithms serving customers of, for example, investment banks in stock and currency markets. Finally, entrepreneurship is fundamentally competitive, individualistic and non-solidaristic, whereas 'open innovation' was born from the practices of 'open science' and the collegiate tradition of research. Accordingly, 'entrepreneurial ecosystems' can display more closure than RIS set-ups. This special issue explores aspects of these ecosystem platforms and their implications for emergent forms of urban and regional evolution in the near and nearly present future.